Pilot scale production of sugars from sago starch - Hafizah, Booty (Universiti Malaysia Sarawak (UNIMAS), 2011)
Production of sugars was performed at lab scale (1L) from hydrolysis of various types of starch (sago, corn, tapioca and sweet potato flour). The starch slurries was enzymatically hydrolysed for four hours at the starch concentration of 20% DS (200g of starch powder suspended in 1L water). Filtration of sugar syrup with powdered activated charcoal (PAC) was made and the measurement of glucose was based on the yield referred as dextrose equivalent (DE). Upon filtration, the highest sugar (mainly glucose) recovery was produced by sago starch at 99% DE, followed by corn starch (84% DE), tapioca starch (76% DE) and sweet potato starch (72% DE). The effectsl of different starch concentrations in hydrolysis of sago starch (HSS) were then studied) Evidently, 50% DS generated the highest amount of total reducing sugars (TRS) compared to 40%, 30% and 20% DS at 413 g/L, 377 g/L, 298 g/L, and 205 g/L, respectively. However, the amount of glucose produced from filtered HSS (20% DS) gave the highest recovery (99% DE), a much higher concentration of glucose produced compared to 30% DS (89% DE) and 40% DS (81% DE). Furthermore, the concentration of 50% DS produced the lowest sugar yield at only 63% DE. Enzymatic hydrolysis of sago starch was performed thereafter at a larger scale using 20% DS of sago starch at 5L and 50L working volumes. It was observed that 1,000g of sago starch (suspended in 5L water) yields 66% DE after PAC compared to 62% DE produced from hydrolysed of 10,000g of sago starch. Consequently, scaling up the process from 200g to 1,000g reduced the sugar yield by 33% (99% to 66%), but scaling up further 1,000g to 10,000g reduced the sugars yield by only 4% (66% to 62% DE). These results confirmed that the process could be further scaled up without significant loss in sugar yield. In addition, 60°C was proved to be the best temperature conditions for sugar syrup or hydrolysed sago starch (HSS). Sago starch seems to be the most promising as an alternative raw material for the sugar industry of Malaysia.